RNA Regulated Toxin-Antitoxin Systems in Pathogenic Bacteria - Sarpong, David D.; Murphy, Erin R. (Frontiers in Cellular and Infection Microbiology, 2021)
The dynamic host environment presents a significant hurdle that pathogenic bacteria must overcome to survive and cause diseases. Consequently, these organisms have evolved molecular mechanisms to facilitate adaptation to environmental changes within the infected host. Small RNAs (sRNAs) have been implicated as critical regulators of numerous pathways and systems in pathogenic bacteria, including that of bacterial Toxin-Antitoxin (TA) systems. TA systems are typically composed of two factors, a stable toxin, and a labile antitoxin which functions to protect against the potentially deleterious activity of the associated toxin. Of the six classes of bacterial TA systems characterized to date, the toxin component is always a protein. Type I and Type III TA systems are unique in that the antitoxin in these systems is an RNA molecule, whereas the antitoxin in all other TA systems is a protein. Though hotly debated, the involvement of TA systems in bacterial physiology is recognized by several studies, with the Type II TA system being the most extensively studied to date. This review focuses on RNA-regulated TA systems, highlighting the role of Type I and Type III TA systems in several pathogenic bacteria.